Computing Medoids in Large Spatial Datasets - MOURATIDIS, Kyriakos (Institutional Knowledge at Singapore Management University, 2009)
In this chapter, we consider a class of queries that arise in spatial decision making and resource allocation applications. Assume that a company wants to open a number of warehouses in a city. Let P be the set of residential blocks in the city. P represents customer locations to be potentially served by the company. At the same time, P also comprises the candidate warehouse locations because the warehouses themselves must be opened in some residential blocks.